Answer:
<u>It</u><u> </u><u>is</u><u> </u><u>(</u><u>x</u><u> </u><u>-</u><u> </u><u>3</u><u>)</u><u>³</u><u> </u><u>-</u><u> </u><u>9</u><u>x</u><u>(</u><u>3</u><u> </u><u>-</u><u> </u><u>x</u><u>)</u>
Step-by-step explanation:
Express 27 in terms of cubes, 27 = 3³:

From trinomial expansion:

open first two brackets to get a quadratic equation:

expand further:

take y to be 3, then substitute:

the answer to this question would be c- 15.6
When simplified,letter A will be your answer.
4-7x=15
Answer: Find the negative reciprocal of the slope of the original line and use the slope-intercept form y=mx+b to find the line perpendicular to y=1/5x−1. y=−5x−17